El zafiro de Morgana, il migliore che si vide. - de Riquer, Isabel (Scripta, 2022)
Morgan le Fay donates to Guillem de Torroella a sapphire ring, which enables him to see and speak to King Arthur. Composing this short, yet transcendental, episode of La faula, the author skillfully combined his extensive knowledge of medieval Arthurian literature with data originating from certain lapidaries. The latter (in Latin, French and Catalan) had been read and used in the courtly and medical circles of the Crown of Aragon.